2003
DOI: 10.1046/j.1523-1755.2003.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptors and renal sodium handling in hypertensive fructose-fed rats

Abstract: Fructose-fed rats appear to have lost the feedback mechanism that limits insulin-induced sodium retention through a down-regulation of the renal insulin receptor when the dietary NaCl content is increased. This abnormality might possibly contribute to the elevation of blood pressure in these rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 35 publications
(54 reference statements)
4
75
2
2
Order By: Relevance
“…However, there is some controversy about fructose-induced hypertension, mainly related to the potential to develop hypertension, and many potential explanations for the discrepancy in these findings have been offered, such as differences in the techniques used to measure BP and the feed or drinking conditions. 3,24 In particular, most studies have found that administering rats 10% fructose in drinking water induces a more severe metabolic disorder compared with providing 60% fructose in food. 22,24 In this study, we used 10% fructose in drinking water as a fructose-induced hypertension model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is some controversy about fructose-induced hypertension, mainly related to the potential to develop hypertension, and many potential explanations for the discrepancy in these findings have been offered, such as differences in the techniques used to measure BP and the feed or drinking conditions. 3,24 In particular, most studies have found that administering rats 10% fructose in drinking water induces a more severe metabolic disorder compared with providing 60% fructose in food. 22,24 In this study, we used 10% fructose in drinking water as a fructose-induced hypertension model.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible catheter of the transmitter was surgically 36 secured in the abdominal aorta just below the renal arteries and pointed upstream (against the 37 flow), and the transmitter was sutured to the abdominal wall. The rats were housed in 38 3 individual cages following the operation. For data acquisition, each cage was placed over a 1 receiver panel, which was connected to the personal computer.…”
Section: Radio-telemetry Monitoring Of Blood Pressure 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IR phosphorylation in response to an acute insulin challenge might be a more sensitive test of IR signaling capacity in these rats. We have planned future studies using this approach to evaluate more comprehensively renal IR signaling Conversely, studies by Sechi BASIC RESEARCH www.jasn.org and associates 16 suggest that there is less insulin desensitization of the renal IR relative to other tissues. They examined the binding of labeled insulin, rather than solely expression, and concluded that there were no differences in IR number in the kidneys of fructosefed, insulin-resistant rats relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the renal complications and local GH-IGF axis changes in type 2 diabetes mellitus may be affected to a greater degree by the local diabetic environment, which may lead to the upregulation of glucose transporters, such as solute carrier family 2 (facilitated glucose transporter), member 1 (previously known as GLUT1) [33], or the activation of the diacylglycerol-protein kinase C-extracellular signal-regulated kinase pathway by hyperglycaemia [34]. Possible interventions in this model could then include an improvement in renal insulin signalling [35,36]. This is exemplified by the use of insulin sensitisers in humans, such as peroxisome proliferator-activated receptor gamma agonists, which have been beneficial in the treatment of renal injury in early diabetic nephropathy [37,38].…”
Section: Discussionmentioning
confidence: 99%